2022
DOI: 10.1186/s12903-022-02508-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and oral health behavior, periodontal complaints and oral health-related quality of life in pregnant women

Abstract: Objectives This questionnaire-based cross-sectional study aimed in the evaluation of oral hygiene and oral health behavior, periodontal complaints and oral health-related quality of life (OHRQoL) in pregnant women in southwest-Saxony, Germany. Materials and methods Consecutive patients attending the clinics for Obstetrics and Gynecology, Heinrich-Braun-Klinikum Zwickau, Germany, were recruited in the years 2020 and 2021. The evaluation consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
2
7
0
2
Order By: Relevance
“…The need for dental care during pregnancy recommended internationally has been followed by nations worldwide [ 1 ], as oral health is an important indicator of overall health, well-being, and life quality [ 2 ]. Pregnancy is a period of particular vulnerability because many physiological changes in the body of pregnant women can affect the oral cavity [ 3 ]. In addition, the gestation period presents both physiological and psychological changes that expose the oral cavity to pathologies that can affect the mother’s general health, such as hormonal changes that interfere with the oral cavity, aggravating pathologies like periodontal disease, gingivitis, and dental caries [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for dental care during pregnancy recommended internationally has been followed by nations worldwide [ 1 ], as oral health is an important indicator of overall health, well-being, and life quality [ 2 ]. Pregnancy is a period of particular vulnerability because many physiological changes in the body of pregnant women can affect the oral cavity [ 3 ]. In addition, the gestation period presents both physiological and psychological changes that expose the oral cavity to pathologies that can affect the mother’s general health, such as hormonal changes that interfere with the oral cavity, aggravating pathologies like periodontal disease, gingivitis, and dental caries [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, children whose mothers or caregivers have untreated dental caries were more likely to have dental caries including early childhood caries, the most common chronic infectious childhood disease, and a major public health problem in the coming years [ 5 ]. Previous studies have shown a reduced oral health-related quality of life in pregnant women [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring oral health indicators during prenatal care allows for early intervention, potentially mitigating the risk of pregnancy-related complications [56]. Educating pregnant women about the importance of oral hygiene practices and regular dental check-ups is crucial in preventing potential complications [57]. Implementing comprehensive oral health education programs can empower women to adopt preventive measures and enhance their overall well-being during pregnancy [58].…”
Section: Clinical Implications and Applications Of Dscs In Oral Healthmentioning
confidence: 99%
“…Furthermore, in combination with oral pathological flora, an increased hormone level changes and decreases immune response is shown [ 7 ]. It leads to gums swelling and spontaneous or provoked gingival bleeding [ 8 ]. Although the plaque levels is declared to remain unchanged during the pregnancy, the gingival inflammation of pregnant women is significantly increased and peaked in the third trimester but dropped only at 3 months postpartum [ 7 ].…”
Section: Introductionmentioning
confidence: 99%